Effect of dietry carrot meal supplementation on productivity and carcass characteristics of arbor acre broiler chickens - Mokgope, Precious Kgomotso (University of Limpopo, 2014)
This study determined the effect of carrot meal supplementation on productivity and carcass characteristics of Arbor acres broiler chickens aged one to six weeks. Experiment I determined the effect of carrot meal supplementation on productivity of Arbor acre broiler chicks aged one to 21 days. Two hundred unsexed Arbor acre broiler chickens were randomly assigned to five treatments with five replicates, each replicate having ten birds. A completely randomized design was used in the first experiment. The treatments were 0 (UA0), 20 (AU20), 50 (AU50), 75 (AU75) or 100 (AU100) g of carrot meal supplementation per kg DM feed. Quadratic equations were used to determine levels of carrot meal supplementation for optimal feed intake, metabolisable energy intake and nitrogen retention of Arbor acre broiler chickens aged one to 21 days. Linear equations were used to determine relationships between carrot meal supplementation and productivity variables. Dietary carrot meal supplementation had no (P>0.05) effect on growth rate, live weight and feed conversion ratio of unsexed Arbor acre broiler chickens aged one to 21 days. Carrot meal supplementation, however, improved (P<0.05) metabolisable energy intake and nitrogen retention of the chickens. Dietary metabolisable energy intake and nitrogen retention of the chickens were optimized at different carrot meal supplementation levels of 40.5 and 53.57 g/kg DM feed, respectively. No chicken deaths were recorded. Experiment II determined the effect of carrot meal supplementation on productivity and carcass characteristics of female Arbor acre broiler chickens aged 22 to 42 days. The chickens were randomly allocated to five treatments with five replicates, each having 10 birds, in a completely randomized design. The supplementation levels were 0 (FA0), 20 (FA20), 50 (FA50), 75 (FA75), or 100 (FA100) g of carrot meal per kg DM feed. Quadratic equations were used to determine levels of carrot meal supplementation for optimal feed intake, feed conversion ratio, live weight, metabolisable energy intake and nitrogen retention of broiler chickens aged 22 to 42 days. Linear equations were used to determine relationships between carrot meal supplementation and production variables. Dietary carrot meal supplementation had no (P>0.05) effect on growth rate, live weight and carcass parts of female Arbor acre broiler chickens aged 22 to 42 days. Carrot meal supplementation improved (P<0.05) feed intake, feed conversion ratio, metabolisable energy intake and nitrogen retention of Arbor acre broiler chickens aged vi 22 to 42 days. Dietary feed intake, feed conversion ratio, live weight, metabolisable energy intake and nitrogen retention were optimized at different dietary carrot meal supplementation levels of 52.8, 63.8, 38.0, 42.0 and 44.3 g/kg DM feed, respectively. Dietary carrot meal supplementation had no effect (P>0.05) on tenderness and flavour of female Arbor acre broiler meat. Broiler chickens on diets supplemented with 20, 50 or 100 g of carrot meal per kg DM feed produced meat with better (P<0.05) juiciness values than those of meat from chickens not supplemented with dietary carrot meal and those supplemented with 75 g/kg DM feed. There was a positive relationship between carrot meal supplementation and chicken meat juiciness. It is concluded that carrot meal supplementation improved (P<0.05) metabolisable energy intake and nitrogen retention of unsexed Arbor acre broiler chickens aged one to 21 days. However, carrot meal supplementation had no effect (P>0.05) on growth rate, live weight and feed conversion ratio of unsexed Arbor acre broiler chickens aged one to 21 days. Carrot meal supplementation improved (P<0.05) intake, feed conversion ratio, metabolisable energy and nitrogen retention of female Arbor acre broiler chickens aged 22 to 42 days. However, carrot meal supplementation did not (P>0.05) improve growth rate and live weights of the chickens.
Thesis (MA. Agricultural Management (Animal Production)) -- University of Limpopo, 2014
Keywords: Arbor acres broiler chickens; Carrot meal supplementation; 636.50852; Poultry -- Feeding and feeds; Poultry (Chickens) -- Breeding; Chickens -- Breeding